Enterprise Social Media at Work - Signe Sofie Dyrby (Copenhagen Business School (CBS), 2016)
This PhD thesis is concerned with the social dynamics of Enterprise Social Media (ESM) at work. As ESM technologies are making their way on to the organizational scene, knowledge about how to understand and work with these media are in demand. Existing knowledge about ESM in organizations highlights the technological features and the new possibilities for organizational work that these media bring forward. However, the open and perpetual display of organizational connections and conversations on ESM also presents a unique opportunity for studying the role of social interactions and relationships that underlie organizational work on these platforms. The purpose of this PhD thesis is to examine ESM in light of its social dynamics and the implications of these for organizational work. In the context of this research, social dynamics refer to the interactions and relationships between actors in the organization. Conceptually the social dynamics of ESM at work are investigated in the light of three domains of ESM, sociality and work and their intersections. The investigation builds on the empirical setting of three organizations utilizing the ESM technology Yammer and involves the examination of the organizations' use of the platform through methods of interviews and observations onsite and online. The thesis makes three central contributions to our understanding of the social dynamics of ESM at work. First, the thesis adds to existing perspectives on ESM in organizations by integrating the three domains of ESM, sociality and work. While the literature has so far treated these domains separately or in pairs, this research demonstrates how the social dynamics of ESM in organizations arise between the functionalities of the ESM technology, the sociality of the organizational members, and the work practices carried out. Second, the thesis presents a social fabric framework as a way of explaining, interpreting and understanding the social dynamics of ESM at work. Mapping the social fabric of the organization on ESM provides valuable insight into the dynamic and diverse nature of the relationships that form on the platform and how these create the basis of work. Third, the thesis contributes a relational constructivist perspective to the study of the social dynamics of ESM at work that emphasize the study of relationships between actors rather than the study of individual actors. Considering the social dynamics of ESM in organizations through the social fabric framework provides researchers and practitioners with a new way of understanding and theorizing about ESM at work.
hdl:10398/9264
Keywords: 650